Differential effects of anoctamins on intracellular calcium signals. Issue 5 (9th February 2017) - Cabrita, Inês; Benedetto, Roberta; Fonseca, Ana; Wanitchakool, Podchanart; Sirianant, Lalida; Skryabin, Boris V.; Schenk, Laura K.; Pavenstädt, Hermann; Schreiber, Rainer; Kunzelmann, Karl
ABSTRACT: The Ca 2+ ‐activated Cl ‒ channel TMEM16A [anoctamin (ANO)1] is homologous to yeast Ist2 and has been shown to tether the cortical endoplasmic reticulum (ER) to the plasma membrane. We therefore examined whether ANO1 and other members of the ANO family affect intracellular Ca 2+ ([Ca 2+ ]i ) signals. It is shown that expression of ANO1 augments Ca 2+ store release upon stimulation of GPCRs, whereas knockdown of ANO1, or lack of Ano1 expression in Ano1 ‒ / ‒ animals, as shown in an earlier report, inhibits Ca 2+ release. ANO6, and −10 show similar effects, whereas expression of ANO4, −8, and −9 attenuate filling of the ER store. The impact of ANO1 and −4 were examined in more detail. ANO1 colocalized and interacted with IP3 R, whereas ANO4 colocalized with SERCA Ca 2+ pumps and interacted with ORAI‐1 channels, respectively. ANO1 Cl currents were rapidly activated exclusively through Ca 2+ store release, and remained untouched by influx of extracellular Ca 2+ . In contrast expression of ANO4 caused a delayed activation of membrane‐localized ANO6 channels, solely through store‐operated Ca 2+ entry via ORAI. Ca 2+ signals were inhibited by knocking down expression of endogenous ANO1, −5, −6, and −10 and were also reduced in epithelial cells from Ano10 ‒ / ‒ mice. The data suggest that ANOs affect compartmentalized [Ca 2+ ]i signals, which may explain some of the cellular defects related to ANO mutations.—Cabrita, I., Benedetto, R., Fonseca, A., Wanitchakool, P., Sirianant, L., Skryabin, B. V., Schenk, L. K., Pavenstädt, H., Schreiber, R., Kunzelmann, K. Differential effects of anoctamins on intracellular calcium signals. FASEB J. 31, 2123–2134 (2017). www.fasebj.org